Evolution of Risks for Energy Companies from the Energy Efficiency Perspective: The Brazilian Case - Perroni, Marcos; Dalazen, Luciano Luiz; Da Silva, Wesley Vieira; GouvÃªa, Sergio; Da Veiga, Claudimar Pereira (International Journal of Energy Economics and Policy, 2015)
This study aims to evaluate whether energy savings from energy efficiency programs in Brazil affected the risks taken by energy companies during the period 2000–2013, based on the following research question: Can we assume that energy conservation programs affect return risks to electrical energy companies? The results obtained through risk assessment models, exponentially weighted moving averages, and the capital asset pricing model indicated that during periods of crisis, both volatility and required returns were higher, but during less difficult periods, risks taken were significantly reduced. Further, as research contribution, this research suggests the elimination the affirmative hypothesis that a possible increase in energy efficiency affects the risks taken by electrical energy companies. Keywords: Capital Asset Pricing Model; PROCEL, Energy Conservation Programs. JEL Classifications: E30; G38; K23; M48; Q4